A novel process for recovering aluminum and silicon from fly ash in cryolite molten salt. (15th November 2022) - Tao, Wenju; Yang, Jiaxin; Liu, Zhibo; Zhang, Yifan; Chen, Liyu; Wu, Shaohua; Qiao, Jinbo; Xue, Zhengduo; Wang, Zhaowen
Abstract: The recovery and utilization of by-product coal fly ash (CFA) in high-value-added thermal power plants is of great significance. This research focused on producing high-value-added Al–Si master alloy by aluminothermic reduction with coal fly ash as the raw material. The effects of reduction time and reducing agent amount on thermal reduction products were investigated using the single factor method. X-ray diffraction (XRD) and scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) results showed that Al, Si, and a small amount of Fe were the main components of the alloy. With an increase in reaction time, the mass fraction of Si in the product increased from 4.41% to 9.93%. Besides, the molten salt after thermal reduction was recovered by the electrochemical reduction process. The results showed that a longer electrolysis time is more conducive to improving the recovery of Si and Al. The results of cyclic voltammetry and electrodeposition showed that Si would be reduced in a multi-step process. Combined with thermal reduction and electrochemical secondary recovery process, the comprehensive recovery of Al and Si in fly ash could reach 87.33% and 84.02%, respectively. Graphical abstract: Image 1 Highlights: A novel approach combines the technology of aluminothermic reduction and electrolysis. The remaining waste molten salt from the aluminothermic reduction can be further recovered. The thermokinetics and mechanism of the technological process were analyzed. The recovery of Al and Si in fly ash could reach 87.33% and 84.02%, respectively.